PENGGUNAAN STRATEGI MNEMONIK DALAM MEMPELAJARI KOSAKATA BAHASA JERMAN PADA SISWA KELAS X SMA NEGERI 1 GEDANGAN - Zahara, Arjun Idam; Samsul, Suwarno Imam (LATERNE, 2022)
German is one of the second languages studied in Indonesia. To be able to speak, students must master four basic skills, namely: reading, writing, listening and speaking. These four skills cannot be separated from the fundamental language element, namely vocabulary. To be able to learn vocabulary takes a lot of time. But on the other hand, the COVID-19 pandemic has pushed schools in Indonesia to cut class hours, resulting in learning unable to run effectively. To answer these problems, this study was made to test alternative methods that can be used. This study focuses on testing the effectiveness of mnemonic strategies and comparing them with conventional methods. This research was conducted on the tenth-grade students of SMA Negeri 1 Gedangan using the two-group pretest-posttest method which was determined by purposive sampling. Each experimental and control group received three consecutive meetings, pretest, treatment, and posttest. The control class received teach using conventional methods and the experimental class received teaching using mnemonic strategies. The pretest and posttest consisted of 20 items containing text and conversation to determine the contextual understanding of W-Frage vocabulary. The pretest and posttest results obtained were then analyzed with the SPSS statistical program. From the results of the paired-sample t-test analysis, it is known that the conventional method and the mnemonic strategy both have a positive impact. While the results of the independent sample t-test analysis showed a significance value of 0.88 (equal variances assumed) and 0.93 (unequal variances assumed) > 0.05 so that H0 was accepted and H1 was rejected. These results are not in accordance with the theoretical review of previous research, so a review was carried out which found that the two control and experimental classes were not homogeneous or unequal, which much influenced the results of the analysis